COMPUTATIONAL ASSESSMENT OF THE ADME-TOX PROFILES AND HARMFUL EFFECTS OF THE MOST COMMON USED PHTHALATES ON THE HUMAN HEALTH - CRĂCIUN, Dana; DASCĂLU, Daniela; ISVORAN, Adriana (Studia Universitatis Babeș-Bolyai Chemia, 2019)
In this study, we consider 25 of the most commonly used phthalates and summarize the available data that support their effects on humans. For 15 of the 25 investigated phthalates (60%) there are no human hazard assessment data, neither from experimental nor from computational studies, which underlines the necessity of their risk assessment. Consequently, we have used various computational tools to predict their ADME-Tox profiles and assess their harmful effects on humans. The outcomes of our study reveal that the investigated phthalates have good bioavailability and skin permeability which are associated with toxicity, especially when they are inhaled. They are able to interact with important molecular targets in the human organism such as membrane receptors, cytochromes, kinases, phosphatases, transcription factors, or transporters. These interactions may conduct to predicted harmful effects of phthalates, such as toxicity and irritations of the respiratory and gastrointestinal tracts, skin and eye irritations, endocrine disruption potential, or non-genotoxic carcinogenicity. The investigated phthalates are not predicted to produce genotoxic carcinogenicity, mutagenicity and cardiotoxicity. Beside the investigated phthalates, the di(2-ethylhexyl) phthalate reflects the highest number of toxic effects, and the ditridecyl phthalate and the diisotrodecyl phthalate illustrate the smallest number of possible toxicological effects, namely skin irritation, non-genotoxic carcinogenicity and endocrine disruption potential.